2003
DOI: 10.1055/s-2003-38179
|View full text |Cite
|
Sign up to set email alerts
|

Chorioretinitis Induced by Intravesical Bacillus Calmette-Guérin (BCG) Instillations for Urinary Bladder Carcinoma

Abstract: BCG chorioretinitis is a rare complication that can be seen after intravesical BCG therapy. BCG is a live attenuated strain of Mycobacterium bovis. Two mechanisms can be proposed as the origin of ocular inflammation: a local immune response or a direct choroidal mycobacterial infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 2 publications
(5 reference statements)
2
10
0
Order By: Relevance
“…In this study, a 57 year-old patient developed bilateral ocular lesions that resembled those observed in our patient, following a 6-month course with intravesical BCG with the Connaught strain. Similar to our patient, his choroidal lesions did not progress after therapy with rifampin, isoniazid, and ethambutol [6]. …”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In this study, a 57 year-old patient developed bilateral ocular lesions that resembled those observed in our patient, following a 6-month course with intravesical BCG with the Connaught strain. Similar to our patient, his choroidal lesions did not progress after therapy with rifampin, isoniazid, and ethambutol [6]. …”
Section: Discussionsupporting
confidence: 79%
“…Despite the negative acid fast stain, a high level of suspicion for mycobacterial infection resulted in further testing and the eventual establishment of multiorgan involvement with Mycobacterium bovis BCG. While hepatic, bone marrow, and pulmonary involvement have been extensively documented, the occurrence of mycobacterial choroiditis has only been reported in one prior case report [6]. In this study, a 57 year-old patient developed bilateral ocular lesions that resembled those observed in our patient, following a 6-month course with intravesical BCG with the Connaught strain.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…23 From a pathogenetic point of view, also, reliable animal models have demonstrated that the exposure to mycobacterial antigens (including those of M. bovis) may exacerbate the clinical expression of a pulmonary M. tuberculosis disease (and mycobacterial diseases as a whole) due to the demonstrated immune activation mechanisms, which increase the respiratory inflammation process via the secretion of large amounts of TNF-alpha and other proinflammatory cytokines, concurrently blunting most of the defense mechanism, and the containment of local pulmonary mycobacterial load. 24 After the first relevant survey conduced on over 2600 urologic cancer patients by Lamm et al, 21 single case reports have been published in the international literature regarding anecdotal episodes of respiratory involvement (BCG pneumonia), 22 granulomatous hepatitis, 25,26 renal involvement (granulomatous nephritis), 27 bone marrow invasion concurrent with liver disease, 28 local ocular involvement (corioretinitis), 29 and also vascular damage, mostly represented by aneurismatic lesions (of either native or prosthetic large vessels), 30,31 in 1 single episode associated with vertebral osteomyelitis, too. 31 Finally, secondary to local (i.e., in-…”
Section: Discussionmentioning
confidence: 99%